Re-Desain Edu-Tourism ”Kampung Petualang” di Desa Singapadu Tengah, Kabupaten Gianyar, Bali - I Wayan Parwata; Lilik Antarini; Wesna Astara (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Since the Covid-19 pandemic in Indonesia last March 2, 2020, all service and empowerment activities in 2020 have followed restrictions on direct activities involving large crowds and crowds. The Covid-19 pandemic has devastated all aspects of economic and social life, especially for the tourism world, especially in Bali. Central Singapadu Village, which has only been designated as a Tourism Village in Gianyar Regency since 2018, is one of the newly developed tourist villages with potential that also experiences physical and non-physical problems. The Asset Based Community Development (ABCD) approach emphasizes village potential and the utilization of this potential becomes an opportunity in the development of education, adventure, and resilient tourism villages during the COVID-19 period. This approach focuses on the needs in village development by mapping problems in the community, including partner groups, community leaders and village government.